Opportunity creation: Entrepreneurial agency, interaction, and affect. (6th November 2017) - Goss, David; Sadler‐Smith, Eugene
Abstract : Research Summary : This article addresses opportunity creation, with particular focus on the interplay between social context and individual agency. Using ideas grounded in contemporary micro‐sociology, we offer a conceptual framework that articulates opportunity‐creating agency as the outcome of socially situated subjectivity, supportive or challenging interactions, and the circulation of emotional energy. This dynamic process is illustrated with references to entrepreneur Sir Richard Branson (founder of Virgin). Our article contributes to opportunity creation research by: offering a conception of individual opportunity‐creating propensities rooted in social situations and consistent with constructionist assumptions; specifying the role played by affect/emotion in opportunity creation and positing a novel creative role for negative affect; and connecting opportunity creation with other areas of theoretical interest in entrepreneurship, such as creativity, frustration, and hubris. Managerial summary : This article examines how social relationships and emotions can together influence the ways entrepreneurs initiate and shape opportunities. Using examples from the career of Sir Richard Branson (founder of Virgin), we suggest ways in which the emotional intensity of social interactions can motivate entrepreneurs to act decisively to initiate opportunities for business formation and development. We suggest how this may help us understand not just opportunity creation, but also key entrepreneurial issues, such as creativity, frustration, and hubris.